GR_GERICHTE SR1 2022 41 vom 18. März 2025 , Entscheide Obergericht - GR Gerichte (2025)
grobe Verletzung von Verkehrsregeln gemäss Art. 27 Abs. 1 und Art. 32 Abs. 1 SVG i.V.m. Art. 90 Abs. 2 SVG | Strassenverkehrsgesetz SVG